Pastoral Disabilitas: Ruang Pembebasan bagi Insan dengan Disabilitas di Indonesia - Imanuel Teguh Harisantoso (SANCTUM DOMINE: JURNAL TEOLOGI, 2026)
Existentially, disability pastoral care is a creative space for disabilities. Disability pastoral care is not just a physical space but also a theological reflection and a pastoral practice that can help individuals with disabilities and church institutions (society) find meaning in life and in relationships with others. Literature research becomes a tool to unpack these problems. Based on the cultural belief that pastoral practice has local cultural roots and is grounded in religious traditions, as documented in religious texts. From library studies and theoretical dialectics, the research findings are as follows: first, Biblical texts become the root of the belief in pastoral practice in the church and society; second, the pastoral circle becomes a practical step for the church and pastoral practice practitioners to find, design, and implement disability services; third, that pastoral practice is always connected to religious communities and society as a model of ministry.